Characteristics associated with use of subcutaneous depot medroxyprogesterone acetate (DMPA-SC) in Burkina Faso, Democratic Republic of Congo, and Uganda - Philip Anglewicz; Elizabeth Larson; Pierre Akilimali; Georges Guiella; Patrick Kayembe; Simon P.S. Kibira; Fredrick Makumbi; Scott Radloff (Elsevier, 2021)
Objectives: To what extent is DMPA-SC reaching new users versus encouraging method switching among existing users? Though increasingly-popular, little is known about characteristics of women using DMPA-SC in SSA. We compared characteristics of women using DMPA-SC with those of other modern methods, and identified the extent to which women using DMPA-SC switched from another method or are first-time users of contraception. Study design: We used data collected by the Performance Monitoring for Action (PMA) Project between 2016 and 2019 from three countries, Burkina Faso, Democratic Republic of Congo, and Uganda. We tabulated characteristics of DMPA-SC, DMPA-IM, implant, and male condom users, and used multivariate analysis to compare characteristics of women using DMPA-SC those of the other three methods. We also examined previous contraceptive method use (if any) among women currently using DMPA-SC. Results: We found that never-married women were more likely to use male condoms instead of DMPA-SC. Women with two or more children (compared to no children or one child) were more likely to use implants instead of DMPA-SC in both Uganda and DRC. DMPA-SC was the first method used by the majority of current users in Burkina Faso and Uganda. DMPA-SC users who previously used another method generally switched from less effective methods. Conclusions: Although the characteristics of women using DMPA-SC varied across countries, DMPA-SC appears to be reaching new populations of women instead of inspiring existing modern users to switch to DMPA-SC, and appears to be appealing to first time users of contraception. Implications: It appears that DMPA-SC appeals to new contraceptive users in sub-Saharan Africa, which implies that DMPA-SC may have the potential to increase modern contraceptive prevalence in sub-Saharan African countries.